Dutch and English toddlers' use of linguistic cues in predicting upcoming turn transitions - Lammertink, Imme; Casillas, Marisa; Benders, Titia; Post, Brechtje; Fikkert, Paula (Frontiers in Psychology, 2015)
Adults achieve successful coordination during conversation by using prosodic and lexicosyntactic cues to predict upcoming changes in speakership. We examined the relative weight of these linguistic cues in the prediction of upcoming turn structure by toddlers learning Dutch (Experiment 1; N = 21) and British English (Experiment 2; N = 20) and adult control participants (Dutch: N = 16; English: N = 20). We tracked participants’ anticipatory eye movements as they watched videos of dyadic puppet conversation. We controlled the prosodic and lexicosyntactic cues to turn completion for a subset of the utterances in each conversation to create four types of target utterances (fully incomplete, incomplete syntax, incomplete prosody, and fully complete). All participants (Dutch and English toddlers and adults) used both prosodic and lexicosyntactic cues to anticipate upcoming speaker changes, but weighed lexicosyntactic cues over prosodic ones when the two were pitted against each other. The results suggest that Dutch and English toddlers are already nearly adult-like in their use of prosodic and lexicosyntactic cues in anticipating upcoming turn transitions.